Parental Expectation, Attitudes, and Home Numeracy Environment in Korea and in the U.S.: Potential Sources of Asian Math Advantages - Kyong-Ah Kwon; Haesung Im; Amber Beisly (MDPI AG, 2024)
This present study examined relations among parental math attitudes, expectations, and practice, and preschool children's math achievement (i.e., parental math practice as a mediator) that may differ between Korean and U.S. samples. We examined measurement invariance to minimize the bias and inaccurate estimates in scores in two samples, which is a common barrier in cross-cultural studies. The Korean sample comprised 232 children (mean age = 54.58 months) and their parents from large urban cities and two other provinces. The U.S. sample included 146 preschool children (mean age = 52.49 months) and their parents in an urban area. We utilized measurement invariance to investigate whether the parental math practice has the same meaning across the two samples, along with mediation group comparisons. U.S. parents tended to have more positive math attitudes and higher expectations, while Korean parents were likely to be more involved in math practice with children at home. Korean children scored significantly higher on math achievement than the U.S. children. Among the Korean sample, higher parental math expectations were associated with higher levels of parental math practice, which was, in turn, associated with higher levels of child math outcomes after controlling for child age and SES. On the contrary, parental math expectations were unrelated to their math practice or child math outcomes in the U.S. sample. Parent math attitudes were not associated with any variables in both samples. These findings explain Asian math advantages that emerge early and offer insights into cultural processes (i.e., the importance of parental math practice) that may play a different role in children's math outcomes.